Identification of Community Empowerment Through Sociopreneurship in the Tourist Village of Kubu Gadang - Annisa Ismi Oktaviana Pasaribu (i-Tourism: Jurnal Pariwisata Syariah, 2025)
Kubu Gadang Tourism Village offers a special experience that cannot be found in other tourist attractions. Kubu Gadang Tourism Village itself has implemented a social entrepreneurship-based program that prioritizes economic activities, in terms of profit and social aspects. The role of the community is the key to the growth of Kubu Gadang Tourism Village. Kubu Gadang Tourism Village has implemented community empowerment through tourism village development, as the economy, society, and environment are inherently interconnected with the tourism sector itself. This study aims to investigate how Kubu Gadang Tourism Village implements sociopreneurship by involving the community in its development process, focusing on sociopreneurship objectives through social value, civil society, innovation, and economic activity. Data will be collected through interviews, observations, and document analysis using a qualitative approach. The findings of this research are expected to provide insights for tourism managers to enhance sociopreneurship in the development of future tourist villages.